Why are Some Healthcare Chaplains Registered Professionals and Some are Not? A Survey of Healthcare Chaplains in Scotland. (17th January 2020) - Snowden, Austyn; Enang, Iniobong; Kernohan, W. George; Fraser, Derek; Gibbon, Alan; Macritchie, Iain; McSherry, Wilfred; Ross, Linda; Swinton, John
Abstract : The professional status of UK healthcare chaplains remains partial, with voluntary accreditation effective in achieving around 50% registration. This study set out to elicit reasons for this by surveying healthcare chaplains working in Scotland. An online survey was created to gather demographic details and chaplains' opinions on the importance of five key elements of professional status: A body of knowledge that underpins practice; A code of professional ethics; An occupational organization controlling the profession; Substantial intellectual and practical training; and Provision of a specialized skill or service. Most respondents (38/43) agreed that chaplains should belong to a professional body in order to maintain standards, ensure accountability and formalize professional development. They said that registration reinforced their professional status, added credibility and a clear governance structure to protect the public. However, a minority felt disconnected from the professionalization agenda. This paper discusses the reasons for this. Further UK and international studies into the professional status of chaplains are planned.